Removal of dental alloys and titanium attenuates trace metals and biological effects on liver and kidney. (March 2020) - Pan, Yu; Lin, Yunzhi; Jiang, Lei; Lin, Honglei; Xu, Caiming; Lin, Donghong; Cheng, Hui
Abstract: To determine whether the potential effects on liver and kidney caused by dental alloys could be reduced or terminated by the removal of nickel-chromium (Ni-Cr) alloy, cobalt-chromium (Co-Cr) alloy, and commercially pure titanium (CP-Ti), they were placed in the cheek pouches of Syrian hamsters according to ISO 10993-10. Then, the peak/plateau and end times of trace metals in the blood were determined with or without the removal of the dental alloys. Based on these time points, the trace metals and their effects on liver and kidney were examined. We found that trace metals released from these dental alloys and titanium were accumulated transiently in the blood, liver, and kidney but had no effect on the histopathology of the liver or kidney. Although the functions of the liver and kidney were compromised, the function of these tissues seemed to be clinically acceptable compared to those in control Syrian hamsters. In addition, the apoptotic effect on renal cells was terminated by removing the Ni-Cr and Co-Cr alloys, and that on hepatocytes was also eliminated by removing the Ni-Cr alloy. In contrast, the effect of the Co-Cr alloy on hepatocytes was temporary and recovered by itself. Taken together, Ni- and Co-based dental alloys and titanium have no effect on the histopathology or function of liver and kidney. Moreover, Ni-Cr and Co-Cr alloys induce transient trace metal accumulation and apoptotic effects in liver and kidney, which can be reduced or terminated by the removal of the alloys, while CP-Ti shows favorable biocompatibility. Graphical abstract: Image 1 Highlights: Trace metals released from dental alloys and titanium are accumulated transiently in peripheral blood. Trace metals in peripheral blood decrease sharply after removal of dental alloys and titanium. Ni-Cr and Co-Cr alloys induce transient increment of trace metals and apoptotic effect on liver and kidney. Trace metals and apoptotic effect on liver and kidney are reduced or terminated by removal of dental alloys and titanium. Ni- and Co-based alloys and titanium have no effect on histopathology or function of liver and kidney.